Multifunctional properties of 3D printed poly(lactic acid)/graphene nanocomposites by fused deposition modeling. Issue 1 (2nd January 2017) - Prashantha, K.; Roger, F.
ABSTRACT: In this work, three-dimensional (3D) printing system based on fused deposition modeling (FDM) is used for the fabrication of conductive polymer nanocomposites. This technology consists in the additive multilayer deposition of polymeric nanocomposite based on poly(lactic acid) (PLA) and graphene by means of a in house made low-cost commercial bench-top 3D printer. Further, 3D printed PLA/graphene nanocomposites containing 10 wt% graphene in PLA matrix were characterized for their mechanical, electrical and electromagnetic induction shielding properties of the nanocomposite. Furthermore X-ray computed micro-tomography analyses showed that printed samples have good dimensional accuracy and are significantly closer to the predefined design and the results of scanning electron microscopy (SEM) printed samples showed a uniform dispersion of graphene in PLA matrix The proposed material has uniquely advantageous when implemented in 3D printed structures, because incorporation of multifunctional graphene has been shown to substantially improve the properties of the resulting nanocomposite.